Novel pyrazole-3-carboxamide derivatives as cannabinoid-1 (CB1) antagonists: journey from non-polar to polar amides - Sasmal, Pradip K.; Reddy, D. Srinivasa; Talwar, Rashmi; Venkatesham, B.; Balasubrahmanyam, D.; Kannan, M.; Srinivas, P.; Kumar, K. Shiva; Devi, B. Neelima; Jadhav, Vikram P.; Khan, Sanjoy K.; Mohan, Priya; et al. (Bioorganic & Medicinal Chemistry Letters, 2011)
The synthesis and biological evaluation of novel pyrazole-3-carboxamide derivatives as CB1 antagonists are described. As a part of eastern amide SAR, various chemically diverse motifs were introduced. In general, a range of modifications were well tolerated. Several molecules with high polar surface area were also indentified as potent CB1 receptor antagonists. The in vivo proof of principle for weight loss is exemplified with a lead compound from this series. (C) 2010 Elsevier Ltd. All rights reserved.

Enantiodivergent routes to (+) and (-)-novioses from (-)-pantolactone - Rajesh, B. M.; Shinde, Madhuri V.; Kannan, M.; Srinivas, Gujjary; Iqbal, Javed; Reddy, D. Srinivasa (RSC Advances, 2013)
Noviose, a rare sugar moiety present in many biologically interesting molecules such as novobiocin and tiacumicin was obtained through formal synthesis in (+)- and (-)-forms starting from commercially available (-)-pantolactone in an enantiodivergent manner.